1997
DOI: 10.1177/112067219700700202
|View full text |Cite
|
Sign up to set email alerts
|

Regression and wound Healing after Excimer Laser Prk: A Histopathological Study on Human Corneas

Abstract: Our histopathological results indicate that corneal wound healing after excimer laser PRK varies among individuals. In some people epithelial basement proteins, such as collagen type IV, are the main wound healing products, whereas in others mainly collagen type III is found postoperatively, which does not effect the synthesis of collagen type IV. This suggests the need for individually-tailored postoperative pharmaceutical treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 32 publications
0
6
0
3
Order By: Relevance
“…The presence of type III collagen in the whole cornea was confirmed in the healing monkey cornea [8,33]. Some authors identified this collagen in combination with type V collagen [40], while other studies reported the presence of small portions of type III and type VI collagen after laser treatment [16,17] and type I with type II in the developing chick cornea [11]. The developing human cornea revealed type I collagen within the corneal stroma, limbus, and epithelial basement membrane, type III collagen only during fetal development, and type IV collagen in the basement membrane and in the adult Descemet's membrane [2].…”
Section: Discussionmentioning
confidence: 91%
“…The presence of type III collagen in the whole cornea was confirmed in the healing monkey cornea [8,33]. Some authors identified this collagen in combination with type V collagen [40], while other studies reported the presence of small portions of type III and type VI collagen after laser treatment [16,17] and type I with type II in the developing chick cornea [11]. The developing human cornea revealed type I collagen within the corneal stroma, limbus, and epithelial basement membrane, type III collagen only during fetal development, and type IV collagen in the basement membrane and in the adult Descemet's membrane [2].…”
Section: Discussionmentioning
confidence: 91%
“…36 The use of PRK, particularly PRK retreatment, is associated with haze. [37][38][39][40] This haze has been shown to result from activated keratocytes causing newly synthesized basal membrane proteins and collagen. [40][41][42] Studies have reported haze to be less of a problem after LASEK as the primary treatment and retreatment.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] This haze has been shown to result from activated keratocytes causing newly synthesized basal membrane proteins and collagen. [40][41][42] Studies have reported haze to be less of a problem after LASEK as the primary treatment and retreatment. 6,[43][44][45][46][47] It is not clear whether the epithelial flap is critical for the reduction in haze.…”
Section: Discussionmentioning
confidence: 99%
“…It is a type of collagen present in newborns and active wound healing corneas (Berman 1991). Collagen III has been detected immunohistochemically in primate corneas after PRK (Malley et al 1988;Fantes et al 1990), it has been identified as one component of the haze material deposited under the epithelium after PRK (Lohmann et al 1997), and it has been correlated to myopic regression (Lohmann et al 1997), as well as hyaluronic acid (Fagerholm et al 1994). The level of mRNA for TGF-b1 was also elevated in regression sample 1 (Table 1).…”
Section: Discussionmentioning
confidence: 99%